Pengawasan Internal Terhadap Disiplin Kerja Aparatur Sipil Negara Pada Dinas Sosial Kota Gunungsitoli - Eliagus Telaumbanua; Suka’aro Waruwu; Otanius Laia (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
− Internal control is a process carried out by the board of directors, management and other personnel within an entity, which is designed to provide adequate assurance regarding the achievement of objectives, with internal control creating a good atmosphere so that all duties and responsibilities can be carried out regularly with discipline. better work too.The formulation of the problem in this study is